Cloning and constructing transformation vector carrying IbOr from the sweetpotato (Impomea batatas L.) involved in accumulation of carotenoids - Hương, Hồ Thị; Ninh, Nguyễn Thùy; Thành, Nguyễn Đức (Vietnam Journal of Biotechnology, 2018)
The Orange gene (Or gene) is known as a gene encoding the protein containing a cysteine-rich Zinc finger domain. The Or protein is an important component of the structure that involes in accumulation of carotenoids and enhancing the resistant ability of plant to enviromental stresses. In an attempt to improve the nutritional quality and resistance to adverse environmental conditions of maize, in this article, we present the results on cloning IbOr gene from the sweetpotato cultivar Hoang Long and constructing transformation vectors carrying cloned IbOr gene under control of Ubiquitin (Ubi) or Globulin 1 (Glo1) promoter. The cloned IbOr gene was 942 bp in size and had similarity level of 100% comparing to the IbOr gene that was deposited in GenBank with Accession number HQ828087.1. The IbOr gene from sweedpotato Hoang Long was registered in GenBank under Accession number KX792094.1. The deduced protein consisted of 313 amino acids having Zin finger domain of DnaJ and HSP40 proteins. We have also constructed two transformation vectors pCambia2300/Ubiquitin/IbOr/Nos and pCambia2300/Glo1/IbOr/Nos. These vectors were transformed successfully into Agrobacterium tumefaciens strain C58. The presence of the target gene (IbOr) and promoter (Ubi or Glo1) in the A. tumefaciens strains were confirmed by colony-PCR amplification with respective specific primer pairs and digested by suitable restriction enzymes. These vectors will provide important materials for further gene transfer research for the expression of IbOr gene and production of transgenic maize with ability to accumulate high carotenoids.